Comunicación familiar en la pandemia COVID 19 entre padres e hijos del colegio secundario CRFA N° 60167 Serafín Filomeno Tamshiyacu Fernando Lores 2021 - Vaquero Hidalgo, Adriana (2024)
Answer the inquiry question about what family communication is like in the covid 19 pandemic between parents and children, of the CRFA Secondary School No. 60167 Serafín Filomeno de Tamshiyacu, which was done by determining the level of family communication existing between fathers, mothers and children. of the aforementioned educational institution. For this purpose, the population and sample of the study were made up of 45 fathers and mothers, to whom a questionnaire validated by experts was applied using the survey technique. The type of research used was descriptive accompanied by a non-experimental, univariate, field and cross-sectional design. Conclusion: During the COVID-19 pandemic, family communication levels varied significantly between fathers and mothers. Among parents, 22.2% reported a low level of communication, 55.6% a medium level, and another 22.2% a high level. On the contrary, among mothers, only 4.5% experienced a low level of communication, while the majority, 71.1%, were at a medium level and 28.9% at a high level. These data indicate that mothers showed a greater propensity to have medium or high-level family communication during the pandemic, suggesting that family communication was more effective among mothers compared to fathers.